Europeanization and transnational states : comparing Nordic central governments - Jacobsson, Bengt, 1954- (Routledge advances in European politics, 2004)
A comparative analysis of the impact of the European Union on central government administration: uses a transformative perspective to examine changes as countries adapt to increased EU integration.